Impact of Selected Environment Conditions on the Shrinkage Strains in Respect to Standard Recommendations. Issue 3 (February 2019) - Bacharz, Magdalena; Raczkiewicz, Wioletta
Abstract: The article discusses the issues related to concrete shrinkage. The basic information on the phenomenon is presented as well as the factors that determine the shrinkage are described. Under laboratory conditions, these factors can be imposed and controlled, but in the field, it is not possible to maintain stable environmental conditions. The paper describes the experimental research that allows determining the effect of changes of humidity and ambient temperature on the values of shrinkage strains in concrete samples and verify the obtained results based on the theoretical model included in the Eurocode 2 standard. The shrinkage strains were measured on samples with dimensions 150x150x600 mm, made of C30/37 concrete with Portland cement and limestone aggregate and with water/cement ratio of 0.43. The samples were divided into two groups - the first group of samples was stored in a chamber with set and controlled values of temperature and humidity, and the second group was left in the laboratory hall with freely changing environmental conditions. The shrinkage strains were measured on samples in accordance with the ITB 194/98 for 175 days. A 20 cm base extensometer was used for the strain measurements. The studies of experimental results of the concrete shrinkage strain are presented with a comparative analysis of the results estimated by the guidelines of the standard according to PN-EN 1992-1-1:2008. The obtained results confirmed that the unstable humidity as well as temperature have a significant impact on the course of shrinkage strains in concrete and they both should be taken into consideration during performing concrete elements.